Bases and technical principles in the surgical treatment of mega-esophagus - Pinotti, Henrique Walter; Rivadeneira, Galo Molina; Raia, Arrigo Antonio (Cirugía del Uruguay, 1982)
It is presented an expeience on 322 cases of megaesophagus that were ubmitted to urgical treament. It is pointed outout that in inicial phase of the disease the cardiomiotomy combined with esophagofundopexy is the procedure of chose.